Efficacy of a Single-Session "Empowered Relief" Zoom-Delivered Group Intervention for Chronic Pain: Randomized Controlled Trial Conducted During the COVID-19 Pandemic - Maisa S Ziadni; Lluvia Gonzalez-Castro; Steven Anderson; Parthasarathy Krishnamurthy; Beth D Darnall (JMIR Publications, 2021)
BackgroundCognitive behavioral therapy-pain is an evidence-based treatment for chronic pain that can have significant patient burden, including health care cost, travel, multiple sessions, and lack of access in remote areas. ObjectiveThe study aims to pilot test the efficacy of a single-session videoconference-delivered empowered relief (ER) intervention compared to waitlist control (WLC) conditions among individuals with chronic pain. We hypothesized that ER would be superior to WLC in reducing pain catastrophizing, pain intensity, and other pain-related outcomes at 1-3 months posttreatment. MethodsWe conducted a randomized controlled trial involving a web-based sample of adults (N=104) aged 18-80 years with self-reported chronic pain. Participants were randomized (1:1) to 1 of 2 unblinded study groups: ER (50/104, 48.1%) and WLC (54/104, 51.9%). Participants allocated to ER completed a Zoom-delivered class, and all participants completed follow-up surveys at 2 weeks and 1, 2, and 3 months posttreatment. All the study procedures were performed remotely and electronically. The primary outcome was pain catastrophizing 1-month posttreatment, with pain intensity, pain bothersomeness, and sleep disruption as secondary outcomes. We also report a more rigorous test of the durability of treatment effects at 3 months posttreatment. Data were collected from September 2020 to February 2021 and analyzed using intention-to-treat analysis. The analytic data set included participants (18/101, 17.8% clinic patients; 83/101, 82.1% community) who completed at least one study survey: ER (50/101, 49.5%) and WLC (51/104, 49%). ResultsParticipants (N=101) were 69.3% (70/101) female, with a mean age of 49.76 years (SD 13.90; range 24-78); 32.7% (33/101) had an undergraduate degree and self-reported chronic pain for 3 months. Participants reported high engagement (47/50, 94%), high satisfaction with ER (mean 8.26, SD 1.57; range 0-10), and high satisfaction with the Zoom platform (46/50, 92%). For the between-groups factor, ER was superior to WLC for all primary and secondary outcomes at 3 months posttreatment (highest P<.001), and between-groups Cohen d effect sizes ranged from 0.45 to 0.79, indicating that the superiority was of moderate to substantial clinical importance. At 3 months, clinically meaningful pain catastrophizing scale (PCS) reductions were found for ER but not for WLC (ER: PCS −8.72, 42.25% reduction; WLC: PCS −2.25, 11.13% reduction). ER resulted in significant improvements in pain intensity, sleep disturbance, and clinical improvements in pain bothersomeness. ConclusionsZoom-delivered ER had high participant satisfaction and very high engagement. Among adults with chronic pain, this single-session, Zoom-delivered, skills-based pain class resulted in clinically significant improvement across a range of pain-related outcomes that was sustained at 3 months. Web-based delivery of ER could allow greater accessibility of home-based pain treatment and could address the inconveniences and barriers faced by patients when attempting to receive in-person care. Trial RegistrationClinicalTrials.gov NCT04546685; https://clinicaltrials.gov/ct2/show/NCT04546685